Investigation of the Depth Stability of the Furrow Former of a Saxaul Seed Planter - Auyezov Ongarbay Pirleshovich; Baltaniyazov Adilbay Sarsenbayevich; Tursımuratov Sapar Eshmuratovich; Khojabaev Nurmukhambet Muratbaevich (Zien Journals, 2025)
The article presents analytical expressions for determining the depth stability of the furrow former of a saxaul seed planter and identifies the factors that influence its performance
Keywords: Saxaul seed planter